Practice pattern and use of a novel skin moisturizer containing skin barrier therapy in patients with atopic dermatitis: a cross-sectional survey among dermatologists in India - Abraham, Anil; Ganjoo, Anil; Kapoor, Sheilly; Sharma, Divya; Talathi, Abhay (International Journal of Research in Dermatology, 2021)
Background: Atopic dermatitis is considered as the most common chronic, inflammatory dermatological disorder. Skin barrier dysfunction represents an early pathology of this condition. Various factors contribute to development of such defects. Skin moisturizers remain the mainstay of therapy for AD along with other treatment modalities. Methods: Dermatologists across India were administered a questionnaire consisting of questions related to number of the patients seen with AD every week and their clinical experience regarding the use of novel skin moisturizer containing skin barrier therapy for the management of AD. The responses were analysed as number and percentages. Results: A total of 1605 patients were included in this survey. The complete responses were obtained from a total of 58 dermatologists. The majority (98%) of the dermatologists found the overall efficacy of novel skin moisturizer (Atoderm Intensive Baume) in AD patients as ‘satisfactory’. Atoderm Intensive Baume was found as efficacious in improving various parameters of AD such as skin dryness, severity of pruritus, inflammation, insomnia, itching, and urge to scratch. It was also well tolerated. It plays an important role in the repair of damaged skin barrier caused by AD. Conclusions: This survey findings indicated that novel skin moisturizer (Atoderm Intensive Baume) is a preferred formulation by dermatologists across India for the management of AD with proven efficacy and safety.